DEVELOPING DIGITAL EYEWITNESS GAME AS A MEDIA TO TEACH WRITING RECOUNT TEXT FOR THE TENTH GRADE STUDENTS IN SMA NEGERI 1 PERBAUNGAN - Fajar Fadli; Sumarsih Sumarsih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
The objective of this study is to develop digital Eyewitness game as a media to teach writing recount text for the tenth grade students in SMA Negeri 1 Perbaungan. This study was conducted by using Research and Development design through six stages; gathering data and information, need analysis, designing materials and media, validating, revising (final product). The subject of the study was tenth grade students and the English teacher in SMAN 1 Perbaungan. The data were gathered by reviewing documents, conducting interview to English teacher and distributing questionnaires to X MIA 1 consisting of 35 students to get the students’ need. The interview and questionnaire results proved that the students needed digital game as a media. The developed reading materials were validated by two experts with the average scores of 92 and 100, it shows that the digital Eyewitness game is valid and suitable to be used for grade tenth students in SMAN 1 Perbaungan. The final product can be downloaded from efllearning-tefl.blogspot.com.Key words: development, digital game, Eyewitness game, recount text.